Could practices of reduced consumption during the COVID-19 pandemic facilitate transformative change for sustainability? Experiences from Sweden and Ireland - Boström, Magnus; Römmelmann, Helena; Sandström, Lina (Frontiers in Sustainability, 2022)
The Covid-19 pandemic implied a disruption of several consumer practices, which offers an opportunity to explore experiences and possibilities to switch towards more sustainable lifestyles with reduced consumption. This article asks if there is long-term transformative potential towards more sustainable and climate friendly consumption practices embedded in these new experiences. By the use of qualitative interviews, the article explores learning experiences gained by “mainstream” consumers in Sweden and Ireland. A theoretical framework consisting of five themes, also related to previous Covid-19 research, guide the analysis of empirical findings: 1) desired objects; 2) confirmation of social relations by non- or alternative consumption; 3) temporal and spatial aspects; 4) de-normalization of mass consumption; 5) new competences and social support. Findings suggest that the long-term lifestyle transformation possibilities are not vast, but neither are they insignificant. Various positive experiences, with implications for reduced/alternative consumption, can be stored in collective memories even if several consumer practices bounce back to ‘normal’ after the pandemic. Based on the findings, the long-term transformative potential is discussed through the lenses of transformative learning, reflectivity, and adaptative abilities. The study contributes to the literature on sustainable and reduced consumption, including literature on degrowth, sufficiency, and downsizing.